Osmocondicionamento na germinação e vigor de sementes de pinhão-manso - Gusatto, Fabiane Cristina (2012)
Jatropha curcas is a shrub with high potential for biodiesel production, formation of roads, fences, trees, grown in semi-arid, and can measure two to three meters in height and 20 centimeters. The preconditioning of seeds is to control the imbibitions of aqueous solutions, until there is osmotic equilibrium, increasing the speed and percentage of germination and seedling emergence, not interfering in the seed so toxic. Thus, this study aims to evaluate the effect of preconditioning in the speed of germination and emergence of seeds of Jatropha curcas L. stored. We used seeds will not benefit of Jatropha curcas from Dourados (MS), for the first test and for the following they were dried in the sun and shade. We analyzed the water content, mass and size of one thousand seeds. The seeds were placed in a glass container and stored in cold chamber at 13ºC for different periods: 0,90, 180, 270, and 360 days. After each storage period, seeds were preconditioned with polyethylene glycol 6000 at 35ºC with concentrations of -0.2 MPa, 0.6 MPa, MPa -1.0, -1.4 MPa and the witness 0 MPa. Germination tests were performed on sand and evaluated the rate of emergence speed and percentage of germination. Sun-drying is best, generates higher rates of germination, with preconditioning temperature of 35ºC, the potentials of -1,4 MPa, in the sun and shade -1,0 MPa for 180 days of storage in glass chamber